Recurrent diffuse panbronchiolitis after lung transplantation: Off-label use of inhaled tobramycin for Pseudomonas aeruginosa control in a transplant recipient - Shin Tanaka; Tuyoshi Ryuko; Yasuaki Tomioka; Kazuhiko Shien; Ken Suzawa; Kentaroh Miyoshi; Hideharu Hagiya; Mikio Okazaki; Seiichiro Sugimoto; Shinichi Toyooka (International Journal of Infectious Diseases)
Objectives: This report highlights a clinical case of recurrent diffuse panbronchiolitis (DPB) after bilateral lung transplantation (LTx), with a focus on the therapeutic impact of off-label inhaled tobramycin solution for inhalation (TSI) in managing Pseudomonas aeruginosa colonization. Methods: A Japanese woman with a history of DPB experienced disease recurrence following bilateral LTx. Persistent colonization by P. aeruginosa and recurrent respiratory symptoms were observed. Off-label TSI therapy, commonly used in cystic fibrosis, was introduced. Clinical response was assessed through radiologic imaging, bronchoscopy, and microbiological cultures. Results: TSI administration led to significant clinical and radiological improvement. P. aeruginosa was eradicated from sputum cultures within one month and remained absent throughout six months of follow-up. No hospitalizations or adverse events were reported during therapy. Conclusion: This case suggests the potential of TSI as a therapeutic approach for managing recurrent DPB and indicates its role in stabilizing post-transplant outcomes. Further studies may clarify its efficacy and expand its application in broader DPB management strategies.